2011
DOI: 10.1111/j.2044-8341.2011.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

A psychotherapeutic baby clinic in a hostel for homeless families: Practice and evaluation

Abstract: Objectives: A pilot baby clinic in a hostel for homeless families has been established to address the specific attachment and developmental needs of infants living in temporary accommodation. The aim of this study was to assess whether this clinic model was associated with more positive outcomes than mainstream community services in terms of infant development and parent-infant interactions.Design: Parent-infant psychotherapy and health visiting services collaborated to develop a new model of baby clinic which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 63 publications
0
14
0
11
Order By: Relevance
“…Inadequate and insecure housing conditions (like mould growth, indoor air pollution, ine ciency of heating systems or lack of sanitation amenities) may trigger many health problems (40). It has already been reported that the prevalence of mental disorders, respiratory and gastrointestinal diseases are high in people living in insecure and inadequate living conditions (26)(27)(28). The prevalence of chronic diseases was the lowest in these two groups in our study compared to the roo ess and houseless groups.…”
Section: Discussionmentioning
confidence: 45%
“…Inadequate and insecure housing conditions (like mould growth, indoor air pollution, ine ciency of heating systems or lack of sanitation amenities) may trigger many health problems (40). It has already been reported that the prevalence of mental disorders, respiratory and gastrointestinal diseases are high in people living in insecure and inadequate living conditions (26)(27)(28). The prevalence of chronic diseases was the lowest in these two groups in our study compared to the roo ess and houseless groups.…”
Section: Discussionmentioning
confidence: 45%
“…The eight included studies investigated the effectiveness of PIP with a range of clinical groups, including depressed mothers (Cicchetti 1999a; Cooper 2003a); maltreating parents (Cicchetti 2006b); incarcerated mother‐infant dyads (Sleed 2013b); parents experiencing a range of infant problems (Cohen 1999b; Robert‐Tissot 1996a); mothers with concerns about their own role as mothers, well‐being of the infants, or the mother‐infant relationship (Salomonsson 2011a); and parents of infants at risk of anxious attachment because their mothers are emotionally unavailable (Lieberman 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Desses 68 artigos excluídos, 32 buscaram avaliar a eficácia e/ou efeitos de intervenções com mães de bebês e/ou famílias de bebês e/ ou profissionais de saúde em diferentes contextos, sem configurar psicoterapia pais-bebê; 12 artigos buscaram analisar a interação mãe-bebê; oito buscaram avaliar resultados e /ou propriedades e/ ou eficácia de instrumentos de avaliação psicológica com a díade mãe-bebê; sete estudos investigaram a saúde mental e/ou problemas de desenvolvimento de crianças; seis buscaram examinar a saúde mental dos pais; dois examinaram fenômenos relacionados à vacinação dos bebês, e um artigo procurou explorar as primeiras experiências de pais que têm um bebê muito prematuro. Dos dez artigos incluídos para este estudo, três deles avaliaram os efeitos de uma intervenção breve em psicoterapia pais-bebê para mães e bebês de populações consideradas de alto risco para a parentalidade (prisões e albergues) (Sleed, Baradon, & Fonagy, 2013a;Sleed, James, Baradon, Newbery, & Fonagy, 2013b;Bain, 2014); um avaliou a eficácia de uma intervenção em psicoterapia utilizando o dispositivo da arte para mães-bebê em um serviço de saúde pública (Armstrong & Howatson, 2015); três artigos analisaram o efeito de uma psicoterapia breve pais-bebê em serviços de saúde pública (Moayedoddin, Moser, & Nanzer, 2013;Salomonsson, Sorjonen, & Salomonsson, 2015;Salomonsson & Sandell, 2011); um artigo avaliou a participação do pai na psicoterapia breve pais-bebê no contexto da depressão pós-parto (Silva, Prado, & Piccinini, 2013); um artigo analisou e identificou conteúdos manifestos nas sessões de psicoterapia breve pais-bebê, evidências empíricas do conceito de "honorável fachada", com base nos eixos conjugalidade e parentalidade (Frizzo, Prado, Linares, & Piccinini, 2011); um artigo demonstrou a organização e o estabelecimento de um serviço de saúde mental para crianças com idade de 0-3 anos, com perspectiva de psicoterapia mãe-bebê em um ambiente comunitário (Berg, 2012).…”
Section: Fluxograma De Busca Nas Bases De Dadosunclassified
“…Referente à primeira subcategoria, designada "artigos cujo objetivo foi identificar os efeitos da intervenção proposta sobre o bebê", destaca-se a análise do desenvolvimento do bebê (motor, cognitivo e emocional), a partir da psicoterapia pais-bebê, em cinco trabalhos (Sleed et al, 2013b;Bain, 2014;Salomonsson et al, 2015;Berg, 2012;Salomonsson & Sandell, 2011); e em outro há a análise do funcionamento global do bebê a partir da psicoterapia pais-bebê (Salomonsson et al, 2015).…”
Section: Fluxograma De Busca Nas Bases De Dadosunclassified
See 1 more Smart Citation